2021
DOI: 10.1097/bor.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

New mechanism-based approaches to treating and evaluating the vasculopathy of scleroderma

Abstract: Purpose of reviewUtilizing recent insight into the vasculopathy of scleroderma (SSc), the review will highlight new opportunities for evaluating and treating the disease by promoting stabilization and protection of the microvasculature.Recent findingsEndothelial junctional signaling initiated by vascular endothelial-cadherin (VE-cadherin) and Tie2 receptors, which are fundamental to promoting vascular health and stability, are disrupted in SSc. This would be expected to not only diminish their protective activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 128 publications
1
14
0
Order By: Relevance
“…The inner layer of blood vessels is lined with endothelial cells that interact with the circulation and are vulnerable to attack by various intrinsic and environmental stimuli. Microbial infection, autoantibodies against endothelial cells, shear stress, oxidative stress, and ischemia/reperfusion injury have been reported as potential contributors to elucidating vascular injury in SSc patients [9]. In this regard, cytomegalovirus infects endothelial cells and monocytes/macrophages, leading to endothelial cell apoptosis and immune system dysregulation, although direct evidence supporting its role in the pathogenesis of SSc is lacking [10].…”
Section: Vascular Injurymentioning
confidence: 99%
“…The inner layer of blood vessels is lined with endothelial cells that interact with the circulation and are vulnerable to attack by various intrinsic and environmental stimuli. Microbial infection, autoantibodies against endothelial cells, shear stress, oxidative stress, and ischemia/reperfusion injury have been reported as potential contributors to elucidating vascular injury in SSc patients [9]. In this regard, cytomegalovirus infects endothelial cells and monocytes/macrophages, leading to endothelial cell apoptosis and immune system dysregulation, although direct evidence supporting its role in the pathogenesis of SSc is lacking [10].…”
Section: Vascular Injurymentioning
confidence: 99%
“…The exact processes of SSc pathogenesis are not clear. However, the pathogenic processes can be summarized in three main events: the endothelial injury with a consequent microvasculopathy, followed by the autoimmune response and inflammation and finally a diffuse fibrosis of skin and internal organs [1][2][3][4][5][6][7][8][9][10][109][110][111][112][113][114][115][116][117][118]. Several studies confirmed the role of each of these three events and their interaction in SSc pathogenesis.…”
Section: Systemic Sclerosis Pathogenesismentioning
confidence: 99%
“…The SSc vascular damage is characterized by the presence of a characteristic processes with a vasomotor instability with an imbalance of vasoactive factors: overproduction of vasoconstrictors (ET-1) and underproduction of vasodilators (NO and prostacyclin) [6][7][8][9][10][11][12][13][22][23][24][25][106][107][108][109]. The free radical nitric oxide (NO) is a potent vasodilator and is synthesized from L-arginine by NO synthase (NOS) [10][11][12][13][14][15][16][17][18][19][22][23][24][25][40][41][42][43][44][45][46][47][48][106][107][108][109][110][111][112][113]. Endothelial isoforms of NOS (eNOS or NOS 3) has been identified with a constitutive expression, other isoforms are shown...…”
Section: The Role Of Endothelial Injury In Systemic Sclerosis Pathoge...mentioning
confidence: 99%
See 2 more Smart Citations